745. Evaluation of a Pharmacist-driven Risk Factor Tool for the Prevention of Hospital-onset Clostridium difficile Infection in a Community Hospital. (4th December 2021) - Weiss, Jennifer; Patel, Gargi; Cavanaugh, Joseph
Abstract: Background: Clostridium difficile infection (CDI) is the most frequently reported nosocomial infection and is the major cause of healthcare and antibiotic associated diarrhea. Guideline recommended preventative strategies include antibiotic stewardship, hand hygiene, barrier precautions, and disinfection of environmental spaces to reduce the risk of hospital onset CDI (HO-CDI); however, there is no standardized scoring method to tactically detect high-risk patients in order to prevent HO-CDI. The objective of this study was to implement a risk stratification procedure for a pharmacist to prospectively identify high-risk patients and make early interventions to prevent the incidence of HO-CDI. Methods: In this single center, ambidirectional cohort study, patients who acquired HO-CDI from January 2019 to June 2020 were identified and evaluated to determine which modifiable risk factors were most prominent. A pharmacist prospectively screened patients who were admitted from October 2020 to February 2021 using a web-based screening tool to detect high-risk patients based on the previously identified risk factors. An interdisciplinary approach was used to make early interventions for high-risk patients such as discontinuation or de-escalation of antibiotics, discontinuation of gastric acid suppression, and early CDI testing before 72 hours of admission. The primary outcome was incidence of HO-CDI per 10, 000 patient days and secondary outcomes were length of hospital stay and duration of non-CDI antibiotic therapy. Appropriate statistical tests were used to measure significance. Results: The primary outcome of HO-CDI cases per 10, 000 patient days occurred at a median rate of 3.95 (IQR 3.38 – 6.30) in the retrospective cohort versus 2.15 (IQR 1.68 – 3.04) in the prospective cohort [p < 0.0125]. There were no significant differences in length of non-CDI antibiotic therapy or length of hospital stay. Baseline Characteristics Primary Outcome Secondary Outcomes Conclusion: In patients at high-risk of developing HO-CDI, pharmacist intervention resulted in a reduced rate of HO-CDI cases per 10, 000 patient days. Disclosures: All Authors : No reported disclosures